Immigration and trade creation for the US: The role of immigrant occupation - Kusum Mundra (Institute for the Study of Labor (IZA), 2012)
This paper highlights that the immigrants' effect on trade is not identical across all types of immigrants but it varies with the immigrants' occupation. Using a sample of 63 U.S. trading partners which are also big immigrant sending countries over the years 1991-2000, this paper finds that the immigrant trade elasticity for the no occupation group is similar in magnitude to the immigrant effect on trade estimated in the literature. However, this does not capture the full extent of the effect of immigrant network on trade. The share of professional immigrants in comparison to immigrants with no occupation significantly increases the trade elasticity for Rauch's referenced price and differentiated commodities and this effect is strongest for the differentiated goods. This paper establishes that immigrants' occupation is an important indicator of the quality and effectiveness of immigrants' network in trade creation with the home country.
Keywords: F22; F11; J10; J61; 330; immigrant occupation; immigrant networks; bilateral trade; U.S.; Migranten; Einwanderung; Beruf; Außenhandelseffekt; Internationale Wirtschaftsbeziehungen; USA